Perubahan Kanji dan Gula dalam Proses Kematangan Buah-buahan. - Mahmood, Marziah (1984)
The content of starch and total SU/lars in bananas, papayas and oranges at different ages and stages of maturity have been determined. In all the fruits studied, the starch content was found to be high in y·ounger fr~its and then began to decrease as the fruits matured and ripened. Comparing all the three types of fruits studied, bananas seemed to have the highest starch content followed by papayas and oranges. The levels of sugars, on the other hand, were initially low, then continue to increase until the ripening stage. Papayas (particularly the yellow flesh) appeared to have the highest concentration of sugars, followed by Pisang Berangan, oranges and Pisang Nangka. The rates of starch and sugar changes varied with fruit types and varieties